2020
DOI: 10.4102/sajhivmed.v21i1.1115
|View full text |Cite
|
Sign up to set email alerts
|

Southern African HIV Clinicians Society guidelines for antiretroviral therapy in adults: 2020 update

Abstract: What is new in the 2020 guidelines update? Key updates ÿ A recommendation for dolutegravir (DTG)-based therapies as the preferred first-line antiretroviral therapy (ART) option (section 11). ÿ Updated guidelines for second-and third-line ART regimens (section 13). ÿ New recommendations on the management of patients on DTG-based therapies who have an elevated viral load (section 12). ÿ A lowering of the threshold for virological failure from 1000 copies/mL to 50 copies/mL (section 8). ÿ A recommendation against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 102 publications
0
47
0
Order By: Relevance
“…Furthermore, this visceral adipose tissue results in accelerated lipolysis and is what contributes to the high prevalence of non-alcoholic fatty liver disease reported in up to 30%-35% of mono-infected patients, that is, PLWH without hepatitis B or C. 34 In the longest follow-up of body composition following ART, it was found that continued fat gain after 96 weeks of treatment was associated with the greatest risk of metabolic disorders. 35 Southern African HIV Clinicians Society guidelines for antiretroviral therapy in adults: 2020 update, 36 now recommend InSTI (Dolutegravir [DTG])-based therapies as the preferred first-line ART therapy. InSTIs have been touted as not affecting cholesterol metabolism which may have a big impact on preventing CVD and GD in these subsets of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this visceral adipose tissue results in accelerated lipolysis and is what contributes to the high prevalence of non-alcoholic fatty liver disease reported in up to 30%-35% of mono-infected patients, that is, PLWH without hepatitis B or C. 34 In the longest follow-up of body composition following ART, it was found that continued fat gain after 96 weeks of treatment was associated with the greatest risk of metabolic disorders. 35 Southern African HIV Clinicians Society guidelines for antiretroviral therapy in adults: 2020 update, 36 now recommend InSTI (Dolutegravir [DTG])-based therapies as the preferred first-line ART therapy. InSTIs have been touted as not affecting cholesterol metabolism which may have a big impact on preventing CVD and GD in these subsets of patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 Only four of the patients had a viral load of < 50, which indicates viral suppression based on the most recent guidelines. 33 All eight patients who were virally suppressed were on first-line therapy. Of the 17 patients who were not virally suppressed, 9 were on FDC (a fixed-dose combination tablet containing tenofovir [TDF] + emtricitabine [FTC] + efavirenz [EFV]); 4 were on first-line treatment, but not FDC; and 3 were on second-line treatment.…”
Section: Resultsmentioning
confidence: 99%
“…50 It is therefore important to diagnose cognitive impairment in PLWH to ensure optimal treatment outcomes and to simplify treatment regimens if possible. Hopefully, the replacement of efavirenz with dolutegravir in the fixed drug combination 33 will lead to more patients with psychiatric disorders initiated on this regimen. Although 32 patients scored lower than 26 on the MoCA, only 4 of these patients were diagnosed with HAND.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa an established IPT protocol exists for HIV positive patients only [ 26 ]. A 12-month duration of IPT is recommended in all non-pregnant HIV positive patients who screened negative for active TB based on symptoms, irrespective of their latent TB status.…”
Section: Methodsmentioning
confidence: 99%